Liquid–Liquid Equilibrium Data and Continuous Process Concept for the Electrosynthesis of Valeric Acid from Levulinic Acid - Rehbein, Moritz C.; Guschakowski, Michael; Sauter, Waldemar; Kunz, Jennifer; Schröder, Uwe; Scholl, Stephan (Frontiers in Energy Research, 2020)
Aiming towards a scalable continuous electrochemical production of valeric acid, the mutual insolubility of valeric acid with the aqueous reaction medium of levulinic acid and the aqueous electrolyte are investigated in order to assess the possibility for an integrated product separation based on the liquid-liquid equilibrium (LLE) of the system. The influence of the electrolyte concentration in the mixture and the mixture temperature on the LLE are studied. Based on these results, the possibility for a batch and a continuous product separation process are developed and discussed.